Lack of Emotional Awareness is Associated with Thwarted Belongingness and Acquired Capability for Suicide in a Military Psychiatric Inpatient Sample. Issue 5 (20th November 2018) - Baer, Margaret M.; LaCroix, Jessica M.; Browne, Joy C.; Hassen, Helena O.; Perera, Kanchana U.; Weaver, Jennifer; Soumoff, Alyssa; Ghahramanlou‐Holloway, Marjan
Abstract : Objective: To examine potential links between facets of impulsivity and emotion dysregulation to components of the Interpersonal‐Psychological Theory of Suicide (thwarted belongingness, perceived burdensomeness, and acquired capability) among U.S. military personnel. Method: The current study performed secondary data analysis from a randomized control trial testing the efficacy of a cognitive therapy for 134 service members (71.64% male, 68.66% Caucasian; mean age: 30.14) admitted to a psychiatric inpatient unit for a suicide‐related crisis. We utilized the Difficulties in Emotion Regulation Scale, the Barratt Impulsivity Scale, the Acquired Capability for Suicide Scale, and the Interpersonal Needs Questionnaire. Results: All emotion dysregulation dimensions and one impulsivity facet (attentional) were positively correlated with perceived burdensomeness and thwarted belongingness. Lack of emotional awareness was positively associated with acquired capability. After controlling for depression, hopelessness, and demographic covariates, lack of emotional awareness was significantly associated with both thwarted belongingness and acquired capability, but not perceived burdensomeness, and impulsivity dimensions did not link to any variable of interest. Conclusions: Findings imply that individuals with reduced emotional awareness may have difficulty cultivating interpersonal bonds and be more vulnerable to elevated acquired capability. Lack of emotional awareness may be a potential contributor to both suicidal desire and capability.